DSDWA: A DCT-based Spatial Domain Digital Watermarking Algorithm - Jianghua Li; Qing Cao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
DCT-based transformed domain watermarking algorithm has some flaws In the aspects of embedding position, embedding strength and embedding method, which have an important influence on watermarking embedding and watermarking extracting. In this paper we discussed these key techniques on DCT-based transformed domain watermarking algorithm and spatial domain digital watermarking algorithm, and their advantages and disadvantages respectively. We discovered the reason that error is generated during DCT and IDCT, and its influence on watermarking embedding and extracting, as well as the basic change rule of the pixel value matrix of the host image during watermarking embedding. On the basis of our analysis, a DCT-based spatial domain digital watermarking algorithm was proposed,which fully leveragedthe discovered change rule during watermarking embedding using DCT-based transformed domain algorithm. Experimental results showed that the algorithm had the advantages of spatial domain algorithm and transformed domain algorithm and overcamesome of their disadvantages. And itt was superior to DCT-base transformed domain watermarking algorithm. In addition, our work has the certain reference significance to other fields using DCT and IDCT. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3323